The oxygen isotope composition of the country rock of the Koegel Fontein igneous complex - Whitehead, Benjamin (Department of Geological Sciences, 2019)
The Koegel Fontein Complex is a Cretaceous anorogenic complex located in southern Namaqualand, west of Bitterfontein, South Africa. The complex comprises a large granite intrusion (the Rietpoort Granite), a series of NW-striking quartz porphyry dykes, and numerous other minor igneous bodies. A breccia plug, and the quartz porphyry dykes have δ18O values as low as -4.1‰, and these are believed to be the result of selective dehydration and melting of previously 18O-depleted rock (Curtis et al., 2013; Olianti and Harris, 2018). This thesis investigates the oxygen isotope composition of the country rock of the Koegel Fontein Complex, which consists of Namaqua-Natal Belt granulite facies rock and minor remnants of overlying Gariep Supergroup metasedimentary rock. The Brak Fontein Shear Zone (BFSZ) is investigated as a protolith for low δ18O (<6 ‰) units of the Koegel Fontein Complex. Geological mapping combined with oxygen isotope data of the country rock confirms that 18Odepletion occurred prior to the emplacement of the Koegel Fontein Complex and is localised in the ~545 Ma BFSZ. Generation of rock with δ18O values as low as -4 ‰ requires a combination of high temperature water-rock interaction, a high water-rock ratio and very low δ18O values in the alteration fluid. Deformation in the BFSZ coincides with the Pan-African Orogeny and a 549-545 Ma global glaciation, and it is reasonable to assume that ambient meteoric water had a very low δ18O value, perhaps as low as -30 ‰. Assuming a possible Δrock-water range from 0.5 to 2.8, a δ18O value of 8‰ for the rock before alteration, a δ18O value of -2‰ for the rock after alteration, a δ18O value of -30‰ for the fluid before fluid-rock exchange and exchange at a temperature range of 400°C to 700°C, a waterrock ratio of ~0.31 to ~0.40 is required to create the observed 18O-depletion in the BFSZ. The calculated water-rock ratio suggests that a significant amount of meteoric water passed through the BFSZ, into the brittle-ductile transition zone. A cold climate only coincides with a suitable tectonic setting during the Pan-African Orogeny, suggesting that the 18O-depletion is syn-tectonic. Furthermore, strong recrystalisation and annealing after deformation and a lack of brittle overprint or cross-cutting fractures and/or veins suggest a low permeability in the BFSZ after the Pan-African deformation. Therefore 18O-depletion in the BFSZ must have occurred during the Pan-African Orogeny and may be evidence for the infiltration of meteoric water into the ductile crust, possibly requiring variable strain rates or seismic pumping.